EQUATIONS FOR GAMMA-RAY ATTENUATION SYSTEMS WITH BEAM DIRECTED VERTICALLY, ALONG GRAVITIONAL FIELD - Elias, Elimoel A. (REVISTA DE AGRICULTURA, 2016)
EQUATIONS FOR GAMMA-RAY ATTENUATION SYSTEMS WITH BEAM DIRECTED VERTICALLY, ALONG GRAVITIONAL FIELD